Oxygen Delivery on Medical Wards - Dickson, Christopher (BMJ Qual Improv Rep, 2015)
Oxygen is used widely used on all medical wards. It is a drug and should be prescribed. There are known problems with over and under delivery of oxygen to patients. Through national audits and recording baseline data locally, compliance with prescribing is low. This has potentially serious patient safety issues. This quality improvement project attempted to improve oxygen prescribing and subsequent dose adjusting on various medical wards. Monitoring showed a transient improvement but this was not sustained. As a result of this project further research will be put into developing the electronic observation chart to set parameters for target saturations.